Large Cell Neuroendocrine Carcinoma of the Lung in Posttuberculosis Cavity - Mansoor C. Abdulla (Indian Journal of Medical Specialities)
A 73-year-old male was admitted with hemoptysis for 2 months. He was diagnosed to have sputum-positive pulmonary tuberculosis 4 years back and was treated with antitubercular drugs for 6 months. Contrast-enhanced computed tomography (CT) of the thorax at that time revealed a cavitary lesion with surrounding consolidation in the right lower lobe of the lung. Contrast-enhanced CT of the chest during present admission showed a mass lesion in the lower lobe of the right lung, which was diagnosed as large cell neuroendocrine carcinoma of the lung on histopathological examination. We describe a patient who developed large cell neuroendocrine carcinoma of the lung in a posttuberculosis cavity which, to our knowledge, is the first such report.